Building an educational program based on computer simulation in - Noah, Souad Abdelsalam; Almousa, Nusaiba Ali (Journal of Educational and Psychological Sciences, 2021)
The research aims at investigating the effect of using a computerized simulation based educational program, in teaching biology for ninth grade students in Jordan, in terms of achievement and tendency for learning. The quasiexperimental design was deployed in this study, along with three tools: a computerized simulation program, an achievement test, and a learning tendency scale. The subjects of the study were randomly selected from two sections of the ninth grade in Al-Nasser Modern School. The first section was treated as an experimental group, consisting of (24) students who were exposed to the computerized simulation program; whereas, the second section was selected as a control group, consisting of (24) students who were exposed to the ordinary instructional program. The results showed that the experimental group (computerized simulation program) obtained an overall average of (20.21 out of 25) in terms of achievement, on the contrary, the control group (the ordinary instructional program) obtained an overall average of (15.17 out of 25) in terms of achievement. Furthermore, the experimental group obtained an average of (3.97 out of 5) in terms of tendency to learn the curriculum, while the control group obtained a total average of (2.58 out of 5) in terms of tendency to learn the curriculum. Therefore, there is a significant difference in both, achievement, and tendency for learning, at the level of (α ≤ 0.05) that can be ascribed to the experimental group. The size of the effect of the post-measurement is (31.6%, for achievement, and (46.4%) for tendency for learning, which means, there is an (average) effect of the computerized simulation program in both. Based on these results, the two researchers recommended adopting this study to benefit from the designated educational program.